Evaluation of Immunological Parameters in Purified Protein Derivative Positive Tuberculin Workers - Shohreh Azimi; Majid Tebianian; Nader Mosavari; Azar Sabokbar; Farhad Jalali; Saba Arshi; Reza Arefpajouhi (Iranian Journal of Basic Medical Sciences, 2013)
Objective(s): According to the occupationally risk of infection in staff workers who have direct contact with mycobacterium species, we investigated their immunological parameters and compared with healthy purified protein derivative (PPD) negative volunteers.   Materials and Methods : We investigated 20 PPD positive volunteers working at Tuberculin Unit of Razi Vaccine and Serum Research Institute and PPD negative healthy controls with no exposure or history of active tuberculosis. The percentages of circulating lymphocyte subpopulations were detected by flowcytometry. IL-4 and IFN-γ production levels were measured by ELISA in supernatants of PPD-stimulated peripheral blood mononuclear cells (PBMCs) culture. Results : Tuberculin workers showed an increase in IFN-γ level and significant decrease of CD4+ T cells percentage and CD4/CD8 ratio compared to PPD negative normal individuals. However the IL-4 production and percentage of other lymphocyte population has been unchanged. Discussion: These observations suggest that the immunological parameters of tuberculin workers with PPD positive reaction, who are occupationally exposed to mycobacterium antigens, could be changed. Future studies will be directed towards cytokine networking and regulatory lymphocytes, which will help us validate the significant data presented in this study.